2001
DOI: 10.1074/jbc.m010735200
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transduction Pathway Underlying Ion Channel Gene Regulation by Sp1-c-Jun Interactions

Abstract: During neuronal differentiation, an exquisitely controlled program of signal transduction events takes place, leading to the temporally and spatially regulated expression of genes associated with the differentiated phenotype. A critical class of genes involved in this phenomenon is that made up of genes encoding neurotransmitter-gated ion channels that play a central role in signal generation and propagation within the nervous system. We used the well established PC12 cell line to investigate the molecular det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…For example, the zif268 promoter is regulated by NGF through a combination of Ras/ERK, PI3K, and JNK cascades (47), whereas the promoters of the chromogranin A gene, the Bcl-2 gene, and the calcitonin generelated peptide gene are targeted solely by Ras/ERK signaling (48,49). Another similar case is seen in NGF regulation of the promoter of the neuronal ␤4 nicotinic acetylcholine receptor gene (50). The present studies suggest that both PI3K and Ras/ERK cascades are involved in the NR1 promoter activation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the zif268 promoter is regulated by NGF through a combination of Ras/ERK, PI3K, and JNK cascades (47), whereas the promoters of the chromogranin A gene, the Bcl-2 gene, and the calcitonin generelated peptide gene are targeted solely by Ras/ERK signaling (48,49). Another similar case is seen in NGF regulation of the promoter of the neuronal ␤4 nicotinic acetylcholine receptor gene (50). The present studies suggest that both PI3K and Ras/ERK cascades are involved in the NR1 promoter activation.…”
Section: Discussionmentioning
confidence: 95%
“…This notion may help to explain the NGF effect on other genes. For example, NGF can up-regulate the promoters of the p21 WAF1/CIP1 and cyclin D1 genes (38) and the ␤4 nicotinic acetylcholine receptor gene (50), where the Ras/ERK is activated and the Sp1 factor is involved. In a recent report, EGF was found to trigger a Ras/ERK cascade that may modify the Sp1 factor and up-regulate the apolipoprotein A-I promoter in a human hepatoma cell line (32).…”
Section: Discussionmentioning
confidence: 99%
“…The zinc finger protein Sp1 participates in the transcriptional regulation of several other NGF-responsive genes (Liu et al, 2001;Melnikova and Gardner, 2001). Functional Sp1 binding elements are located at Ϫ48 and Ϫ168 bp in the rat PNMT promoter , and we have shown that the Ϫ48 bp Sp1 site contributes to the cooperative activation of the PNMT promoter by PKA and PKC .…”
mentioning
confidence: 78%
“…In this regard, it is important to note that a growing body of evidence suggests that the ␣3 and ␤4 subunit genes may be coordinately expressed, whereas the ␣5 gene may be independently regulated (47, 49 -51). A number of laboratories, including our own, have identified several cis-acting transcriptional regulatory elements (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66) and trans-acting regulatory factors (59,65,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) that are involved in the expression of the clustered nACh receptor subunit genes. The majority of the regulatory elements thus far described are involved in activating transcription and are located upstream of the nACh receptor genes that they regulate.…”
mentioning
confidence: 99%